2018
DOI: 10.18632/oncotarget.23927
|View full text |Cite
|
Sign up to set email alerts
|

Immunodominant antigens that induce Th1 and Th17 responses protect mice againstHelicobacter pyloriinfection

Abstract: Helicobacter pylori has infected more than half of the world's population, causing gastritis, gastric ulcers, gastric mucosa-associated lymphoid tissue lymphoma and gastric cancer. The oral recombinant Helicobacter pylori vaccine currently used has made great progress in addressing this problem, however, its efficacy and longevity still need to be improved. Th1 and Th17 cells play essential roles in local protection against Helicobacter pylori in the stomach mucosa. Additionally, protective immunodominant anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…pylori response [22,25,26]. We found here that the perivascular lymphocyte clusters were "expressways" that allowed immune cell emigration into infected gastric mucosa.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…pylori response [22,25,26]. We found here that the perivascular lymphocyte clusters were "expressways" that allowed immune cell emigration into infected gastric mucosa.…”
mentioning
confidence: 65%
“…Circulating immune cells (such as Th1/Th17 cells) permeate across postcapillary venules and infiltrate into the mucosa to induce protection against mucosal pathogens [4]. The role of Th1/Th17 cell-mediated post immunization gastritis is highlighted in the anti-Helicobacter pylori response [21,22]. Our primary experiment found that new vessels with perivascular lymphocyte clusters emerged in the vaccination region after resolution of GSL vaccination-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that the decline in Treg population may be beneficial, as it may enhance protective immunity against Hp. This hypothesis was supported by the results of research on anti-Hp vaccines, which demonstrated a protective role of Th1/Th17 response 55,61,62. Therefore, it appears that both the Th1 and Th17 responses can be effective in Hp erad-…”
mentioning
confidence: 78%
“…In our previous study, an alum-based vaccine caused granulation formation in the stomach [ 8 ], and we could not ignore the chronic cognitive dysfunction, toxicity and autoimmunity induced by alum adjuvant [ 36 38 ]. In contrast, SF has the advantages of slow release, absorption, and in situ gelatinization in various tissues [ 40 , 41 ], SF has been used as a medicinal transmission system [ 42–44 ] and as a fixed culture of mesenchymal cells in vivo [ 45 ]. In this study, SF, as a vaccine carrier, not only reduced stomach damage but also resulted in pronounced infiltration and generation of gastric intraepithelial CD4+T RM cells.…”
Section: Discussionmentioning
confidence: 99%